Geomorphological and morphotectonic features of the alluvial fans of the nortern part of the Aggitis river - Πέννος, Χ.; Ασταράς, Θ.; Βουβαλίδης, Κ.; Παπαφιλίππου-Πέννου, Ε.; Πεχλιβανίδου, Σ. (Bulletin of the Geological Society of Greece, 2011)
The catchment area of Aggitis River, which forms a part of the wider catchment area of the Strymon River, constitutes a tectonic graben. In the north of the graben, landforms of complex alluvial fans (bajadas) are found. In the present study, the impact of tectonics on the deposition process and on the geomorphological relief of the northern basin of Aggitis. For this purpose, a quantitative analysis of morphological characteristics of the alluvial fans is carried out. Moreover, the geologic and stratigraphic characteristics of the fans were studied and components of the tectonic movements that took place in the study area identified. Through the geomorphological survey an uplift of 24m with a twisting towards the northeast for the Menikio Mountain was determined that took place in the Upper Pleistocene. While, for the Falakro Mountain, an uplift movement and a minimum torsion of approximately 9m towards the S – SE was calculated. The mountains at the East and at the West of Aggitis River were uplifted with different rates. This result is in agreement with the argument for the existence of a tectonic system of horsts and grabens that formed the Aggitis River basin and influenced its later development.